Seasonal butterfly (Lepidoptera: Rhopalocera) abundance in forest edges and hiking trail of Ngluyu Forest, East Java, Indonesia - Tawakkal, Refer Iqbal; Dwi Novitasari,; Muzaki, Farid Kamal; Indah Trisnawati, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Species richness and abundance of butterfly (Lepidoptera: Rhopalocera) can be affected by climatic variables including rainfall cycles and other seasonal changes, i.e. availability of food for the larvae and adults. In this study, the hypothesis that the diversity and abundance of butterflies would differ between dry and wet (rainy) season in a tropical forest edges of Ngluyu, Nganjuk Regency, East Java, Indonesia was tested. The belt transect method was used for butterfly inventory along hiking trail and forest edges, and the observation was conducted several times from May 2019 to August 2020. A total of 85 species from five families were recorded, showing species dominance of Nymphalidae (35 species), followed by Lycaenidae (21 species), Pieridae (13 species), Hesperiidae (9 species) and Papilionidae (7 species). At the rainy season (November 2019 and February 2020), 60-62 species were recorded whereas 48- 51 species recorded at dry season (May 2019 and August 2020). Butterfly diversity considered as high with the Shannon-Wiener diversity index (H’) ranged from 3.32-3.51. The dominant species are somewhat similar among observation periods and composed by Caleta roxus (F. Lycaenidae), Euploea camaralzeman, E. tulliolus and Mycalesis janardana (Family: Nymphalidae), Eurema blanda, E. hecabe and Zizula hylax (Family: Pieridae). Based on the study results, butterfly community assemblages showed no difference in species composition between hiking trail and forest edges or between seasons. However, species richness and abundance is much higher in rainy season compared to dry season. An Indonesian endemic butterfly, the Tanaecia trigerta with relatively high abundance in hiking trail area was also found. Regarding to the finding, more appropriate butterfly conservation efforts are needed.